Nicotinic Acid Adenine Dinucleotide Phosphate (Naadp(+)) Is an Essential Regulator of T-Lymphocyte Ca(2+)-Signaling - Berg, Ingeborg (The Rockefeller University Press, 2000)
Microinjection of human Jurkat T-lymphocytes with nicotinic acid adenine dinucleotide phosphate (NAADP(+)) dose-dependently stimulated intracellular Ca(2+)-signaling. At a concentration of 10 nM NAADP(+) evoked repetitive and long-lasting Ca(2+)-oscillations of low amplitude, whereas at 50 and 100 nM, a rapid and high initial Ca(2+)-peak followed by trains of smaller Ca(2+)-oscillations was observed. Higher concentrations of NAADP(+) (1 and 10 μM) gradually reduced the initial Ca(2+)-peak, and a complete self-inactivation of Ca(2+)-signals was seen at 100 μM. The effect of NAADP(+) was specific as it was not observed with nicotinamide adenine dinucleotide phosphate. Both inositol 1,4,5-trisphosphate– and cyclic adenosine diphosphoribose–mediated Ca(2+)-signaling were efficiently inhibited by coinjection of a self-inactivating concentration of NAADP(+). Most importantly, microinjection of a self-inactivating concentration of NAADP(+) completely abolished subsequent stimulation of Ca(2+)-signaling via the T cell receptor/CD3 complex, indicating that a functional NAADP(+) Ca(2+)-release system is essential for T-lymphocyte Ca(2+)-signaling.